2021
DOI: 10.3389/fcell.2021.747057
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181a Targets RSPO2 and Regulates Bone Morphogenetic Protein – WNT Signaling Crosstalk During Chondrogenic Differentiation of Mesenchymal Stromal Cells

Abstract: Mechanisms of WNT and bone morphogenetic protein (BMP) signaling crosstalk is in the focus of multiple biological studies, and it also has been discovered to play important roles in human mesenchymal stromal cells (MSC) that are of great interest for neocartilage engineering due to their high chondrogenic differentiation potential. However, MSC-derived chondrocytes undergo hypertrophic degeneration that impedes their clinical application for cartilage regeneration. In our previous study, we established that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…We found that the expression of this miRNA increased by 3.17-fold. We also found a significant upregulation of miR182a and b, which have been shown to induce chondrogenesis through mechanisms involving downregulation of the Wnt/β-catenin pathway [36], in association with other miRNAs such as miR-185 (whose expression increased 2.08-fold).…”
Section: Discussionmentioning
confidence: 58%
“…We found that the expression of this miRNA increased by 3.17-fold. We also found a significant upregulation of miR182a and b, which have been shown to induce chondrogenesis through mechanisms involving downregulation of the Wnt/β-catenin pathway [36], in association with other miRNAs such as miR-185 (whose expression increased 2.08-fold).…”
Section: Discussionmentioning
confidence: 58%
“…See Table 1 for information about miR‐181 targets in each differentiation lineage. References: [1] (H. Li et al, 2013), [2] (Ouyang et al, 2016), [3] (Z. Zhang et al, 2019), [4] (Knarr et al, 2019), [5] (Chen, Shi, et al, 2016), [6] (Chen, Ning, et al, 2016), [7] (Henao‐Mejia et al, 2013), [8] (C. Z. Chen et al, 2004), [9] (Gabler et al, 2015), [10] (P. Y. Lv, Xu et al, 2020), [11] (Barter et al, 2015), [12] (Vail et al, 2022), [13] (Melnik et al, 2021), [14] (Bakhshandeh, Soleimani, Paylakhi, et al, 2012), [15] (Q. Zhang et al, 2022), [16] (R. Su et al, 2015), [17] (X. Li, Zhang, et al, 2012), [18] (Naguibneva et al, 2006), [19] (Wei et al, 2016), [20] (P. Yuan et al, 2022), [21] (He et al, 2022), [22] (Y. Wang et al, 2020), [23] (Z. Zhao et al, 2019), [24] (Cichocki et al, 2011), [25] (Bhushan et al, 2013), [26] (N. Liu et al, 2020), [27] (Bakhshandeh, Soleimani, Hafizi, et al, 2012), [28] (Zheng, Liu, Tycksen, Nunley and McAlinden 2019), [29] (P. Qi et al, 2021), [30] (P. Y. Lv, Gao, et al, 2020), [31] (Ma et al, 2020), [32] (Y. Liu et al, 2021), [33] (Xie et al, 2018), [34] (B. Zhang et al, 2021), [35] (Shao et al, 2015), [36] (Shao et al, 2018), [37] (Fu et al, 2021), [38] (Han et al, 2020), [39] (Yu et al, 2021), [40] (T. Sun et al, 2019), [41] (G. Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported increased levels of miR‐181a during bone marrow MSC chondrogenesis although a correlation with enhancing hypertrophy was not discussed (Barter et al, 2015; Vail et al, 2022). More recently, Melnik et al identified R‐Spondin 2 ( RSPO2 ) as a key target for miR‐181a in regulating MSC hypertrophy (Melnik et al, 2021).…”
Section: Expression and Function In Skeletal Cell Differentiationmentioning
confidence: 99%
“…A differential expression of miR-181a has also been described in the different stages of maturation of chondrocytes with an upregulation in hypertrophic chondrocytes [3]. It is postulated that miR-181a regulates the balance of WNT and BMP pathways in cartilage [83]. miR-181a also regulates the expression of endogenous CCN1 and ACAN genes with a repressive role in cartilage metabolism via CCN1 as well as ECM construction via aggrecan [84].…”
Section: Discussionmentioning
confidence: 99%